Conformational transitions in ariesaema curvatum lectin: characterization of an acid induced active molten globule - Sharma, Urvashi; Gaikwad, Sushama M.; Suresh, C. G.; Dhuna, Vikram; Singh, Jatinder; Kamboj, Sukhdev Singh (Journal of Fluorescence, 2011)
Biophysical characterization of a lectin from Ariesaema curvatum (ACL) was carried out using steady state as well as time resolved fluorescence and CD spectroscopy under various denaturing conditions. An intermediate with altered tryptophan microenvironment was detected in the phase diagram, which exibited pronounced secondary structure and hemagglutinating activity in presence of 0.25 M Gdn-HCl. An acid induced molten- globule like structure possessing activity and higher thermostability was detected. Transition to the molten globule state was reversible in nature. The lectin retained hemagglutinating activity even after incubation at 95 A degrees C. Both chemical and thermal unfolding of the lectin were found to consist of multistate processes. Fluorescence quenching of ACL was strong with acrylamide and KI. The single tryptophan was found to be surrounded by high density of the positively charged amino acid residues as shown by a ten fold higher K(sv) for KI compared to that for CsCl. The average lifetime of tryptophan fluorescence increased from 1.24 ns in the native state to 1.72 ns in the denatured state.
Keywords: Araceae; Fluorescence lifetime; Hemagglutinin; Molten globule; Secondary structure; Thermostability; Unfolding